Бурозубка альпийская Украинских Карпат - Сеник, А.Ф. (Вестник зоологии, 1967)
Sorex alpinus is a rather rare, scantily explored species of insectivorous. With the purpose of determining 'its subspecific belonging the data of body and skull measurements of 55 individuals were worked out statistically. Sorex alpinus of the investigated territory according to its diagnostic characters is attributed to the smaller subspecies — Sorex alpinus hercynicus Miller, 1909. In the Soviet Carpathians this species is caught in the Chernogory ridge and Beskid hills at the height of 400-1500 m over the sea level. It inhabits the slopes of the hills and the banks of the streams. The author presents the data about the dynamics of population quantity, nutrition, shedding of hair and ectoparasites.